2021
DOI: 10.1016/j.oregeorev.2021.104144
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation into the partition of Mo between aqueous fluids and felsic melts: Implications for the genesis of porphyry Mo ore deposits

Abstract: Most of the world's large molybdenum (Mo) deposits are genetically related to magmas that underwent significant fractional crystallization and fluid exsolution, and the residual silicate melts are commonly peralkaline. To understand the relationship between melt compositions and the genesis of porphyry Mo mineralization, the partition coefficients of molybdenum (D Mo ) between fluid and felsic melt were determined at 850 °C, 900 °C, and 100 MPa with various values of A/NK [molar Al 2 O 3 / (Na 2 O + K 2 O) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…There are somewhat conflicting results in terms of the magnitude of D MVP/melt for Sn, U, Mo, and W, and the importance of complexing agents such as Cl and F. For example, some experimental studies pertaining to upper crustal P-T conditions (e.g., 100-200 MPa, 750-850 o C) suggest that W (Bai and Koster Van Groos, 1999) and Sn (Keppler and Wyllie, 1991;Hu et al, 2008) will be more strongly partitioned into the melt, with D MVP/melt in the range of 10 -4 to 0.5, although results from the same studies suggest that complexing with chloride could be important for both elements. Other studies, including those that measured trapped fluid inclusions in quenched run products, have reported that W (Manning and Henderson, 1984;Keppler and Wyllie, 1991;Schafer et al, 1999;Schmidt et al, 2020), Sn (Schmidt et al, 2020;Zhao et al, 2022), and Mo (Candela and Holland, 1984;Keppler and Wyllie, 1991;Schafer et al, 1999;Tattiche and Blundy, 2017;Jiang et al, 2021) are fluid compatible, with D MVP/melt ranging from ~1 to 35, with evidence for chloride complexing of Sn and Mo. The fluid compatible behavior of W, Sn and Mo is also supported by measurements of coexisting melt and fluid inclusions from natural magmatic suites (Zajacz et al, 2008;Audétat et al, 2000;Audétat et al, 2008;Audétat, 2019), with evidence for chloride complexing of W and Sn.…”
Section: Implications For Element Enrichment Processes In the South M...mentioning
confidence: 99%
“…There are somewhat conflicting results in terms of the magnitude of D MVP/melt for Sn, U, Mo, and W, and the importance of complexing agents such as Cl and F. For example, some experimental studies pertaining to upper crustal P-T conditions (e.g., 100-200 MPa, 750-850 o C) suggest that W (Bai and Koster Van Groos, 1999) and Sn (Keppler and Wyllie, 1991;Hu et al, 2008) will be more strongly partitioned into the melt, with D MVP/melt in the range of 10 -4 to 0.5, although results from the same studies suggest that complexing with chloride could be important for both elements. Other studies, including those that measured trapped fluid inclusions in quenched run products, have reported that W (Manning and Henderson, 1984;Keppler and Wyllie, 1991;Schafer et al, 1999;Schmidt et al, 2020), Sn (Schmidt et al, 2020;Zhao et al, 2022), and Mo (Candela and Holland, 1984;Keppler and Wyllie, 1991;Schafer et al, 1999;Tattiche and Blundy, 2017;Jiang et al, 2021) are fluid compatible, with D MVP/melt ranging from ~1 to 35, with evidence for chloride complexing of Sn and Mo. The fluid compatible behavior of W, Sn and Mo is also supported by measurements of coexisting melt and fluid inclusions from natural magmatic suites (Zajacz et al, 2008;Audétat et al, 2000;Audétat et al, 2008;Audétat, 2019), with evidence for chloride complexing of W and Sn.…”
Section: Implications For Element Enrichment Processes In the South M...mentioning
confidence: 99%
“…Therefore, a high oxygen fugacity has become a widely accepted criterion for distinguishing mineralized and nonmineralized porphyries [34][35][36][37][38][39][40][41][42][43][44]. A high fractionation and oxygen fugacity of the parent magma and enrichment of Mo, S, and H 2 O are favorable conditions for porphyry Mo ore production [45]. However, in some deposits, melts and fluids in mineralization systems have lower Mo contents (2-25 ppm) [30,[46][47][48], indicating conditions for the accumulation and efficient unloading of ore-forming materials, which may be more important than the initial Mo concentration of magma [49].…”
Section: Introductionmentioning
confidence: 99%